Nanosized LaInO3 perovskite for efficient electrocatalytic reduction of CO2 to formate. (February 2023) - Zhu, Yuxiao; Zhou, Wei; Dong, Zichao; Zhang, Xinxin; Chen, Zhipeng; Liu, Ziyong; Li, Fuli; Fan, Jingxin; Jiao, Mingyang; Liu, Licheng
Abstract: Perovskite oxides have been widely used as catalyst due to their ordered structure, diverse chemical range and outstanding properties. However, there are few studies on the application of perovskite oxides in CO2 electrocatalytic reduction reaction (CO2 RR). In this paper, nanosized LaInO3 perovskite catalyst was successfully synthesized and applied to CO2 RR. It displays excellent activity for formate production. The highest faradaic efficiency of formate reaches 91.4 % and the partial current density of formate is 106.8 mA cm −2 at a moderate overpotential of 0.9 V. Additionally, in a wide potential range (−0.8 ∼ −1.3 V vs. RHE), the faradaic efficiency of formate is above 80 %, which is far better than In2 O3 (64.6 %) and the physical mixture of In2 O3 and La2 O3 (63.7 %). The experimental research and DFT calculations indicate that the outstanding activity of LaInO3 is mainly owing to its intensive adsorption stability to free radical intermediates (CO2 ─ ) and lower desorption free energy of formate products during reaction. Graphical Abstract: ga1 Highlights: ● The nanosized LaInO3 perovskite exhibits excellent activity in CO2 RR. ● FE and j of formate can reach up to 91.4 % and 106.8 mA cm −2 at − 1.1 V vs. RHE. ● The weaker adsorption free energy of product account for enhanced activity of LaInO3 .